(untitled) (Quinto Sol, 2020)
The goals of this article are to describe the emergence of the term “Global Health” and to summarize the historical debates around this notion. According to some experts, “Global Health” acquired a prominent role in international health agencies since the late twentieth century. However, some historians doubted of the usefulness of the notion highlighting its relationship with discourses that glorified the neoliberal economic globalization. At the same time, this work analyzes the possibilities for historians of health to use a new paradigm that has recently emerged among health workers and environmentalists known as “Planetary Health”.